2009
DOI: 10.1148/radiol.2512081403
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade Soft-Tissue Sarcomas: Tumor Response Assessment—Pilot Study to Assess the Correlation between Radiologic and Pathologic Response by Using RECIST and Choi Criteria

Abstract: In STS treated with chemotherapy and radiation therapy, tumor size may be insufficient to render actual tumor response. Tumor attenuation at CT or tumor contrast material enhancement at MR imaging may complement tumor size, thus making Choi criteria more predictive of pathologic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 205 publications
(156 citation statements)
references
References 34 publications
7
133
0
16
Order By: Relevance
“…A pilot study in soft tissue sarcoma showed that the Choi criteria were superior to RECIST in assessing treatment response of soft tissue sarcoma treated with chemotherapy and radiotherapy. 7 In this study, we compare RECIST, Choi and "modified" Choi response criteria in which changes in both size and density of target lesions are required to define a response in RCC patients treated with the multi-targeted tyrosine kinase inhibitors sunitinib or cediranib, and their effect on time to progression and survival.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study in soft tissue sarcoma showed that the Choi criteria were superior to RECIST in assessing treatment response of soft tissue sarcoma treated with chemotherapy and radiotherapy. 7 In this study, we compare RECIST, Choi and "modified" Choi response criteria in which changes in both size and density of target lesions are required to define a response in RCC patients treated with the multi-targeted tyrosine kinase inhibitors sunitinib or cediranib, and their effect on time to progression and survival.…”
Section: Discussionmentioning
confidence: 99%
“…29 In this retrospective analysis, we included all patients who entered the study with measurable disease and completed the study protocol treatment; these patients were evaluated before and after treatment by MRI or CT. The current study was conducted on a total of 256 patients, including 143 patients who received neoadjuvant chemotherapy and radiotherapy and 113 patients who received neoadjuvant chemotherapy and adjuvant radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that Choi criteria adapted to magnetic resonance imaging (MRI) correlated better with pathologic tumor response than RECIST in a series of 38 patients with high-grade soft tissue sarcomas who received preoperative chemotherapy with or without radiation therapy within a prospective phase 3 Italian Sarcoma Group/Spanish Sarcoma Group trial. 29 The results of the trial recently were reported. 30 Herein, we evaluate a comparison between RECIST and Choi criteria in eligible patients and correlate response to overall survival (OS) and freedom from progression (FFP).…”
Section: Introductionmentioning
confidence: 99%
“…20) and the Choi criteria, as recently defined for gastrointestinal stromal tumor (GIST; ref. 21) and adapted to MRI (22), and PET response, in case of positive PET at baseline.…”
Section: Clinical Methods and Treatmentmentioning
confidence: 99%